Oral Carcinoma Arising Under Implant-Supported Prosthesis: Progression of Proliferative Verrucous Leukoplakia Initially Mimicking Lichen Planus - Silva, Paula Verona Ragusa [UNESP] (2024)
Proliferative verrucous leukoplakia (PVL) is a non-homogenous type of oral leukoplakia, characterized by multifocal white plaques, propensity to recur after treatment, with strong tendency towards malignant transformation. Interestingly, some studies show that, at initial stages, PVL may resemble oral lichen planus (OLP), potentially leading to misdiagnosis. A 52-year-old woman, with a previous OLP diagnosis, was referred to our service for implant installation and follow-up of OLP lesions. After clinicopathological re-evaluation, a diagnosis of PVL (early stage) was made, and a maxillary full-arch implant-supported prosthesis supported by implants was installed. After 6 years of follow-up, the patient developed squamous cell carcinoma around the implants. The current case emphasizes that PVL patients with oral lesions suggesting peri-implantitis or peri-implant mucositis deserve a more meticulous investigation.